Co- and Post-seismic Deformation Mechanisms of the 2020 Mw6.0 Jiashi Earthquake in Xinjiang (China), Revealed by Sentinel-1 InSAR Observations - Wang, T.; Zhu, S. N.; Yang, C. S.; Wei, Y. J.; Zhao, C.Y.; Hou, H.C. (Frontiers in Environmental Science, 2022)
On January 19, 2020, an Mw6.0 earthquake occurred in Jiashi County, Xinjiang, China. This earthquake is a strong earthquake that occurred in the Kepingtage Belt. The monitoring and inversion of the co-seismic and post-earthquake will help further understand the geometry and movement properties of this tectonic belt. In this study, Sentinel-1A images were used to analyze the deformation of co-seismic and post-seismic events. The Okada elastic dislocation model was used to invert the geometric parameters of the fault and co-seismic slip distribution. The results showed that the maximum uplift and maximum subsidence deformations from the ascending images were 55 and 66 mm, respectively. The maximum uplift and subsidence deformations from the descending images were 73 and 70 mm, respectively. The inversion results show that the earthquake was induced by a fault with a length of 23.5 km, width of 4.7 km, and depth of 7.2 km. This earthquake was a typical dip-slip event. The distributed inversion results of post-earthquake deformation show that the maximum co-seismic slip and maximum post-seismic slip are located on the same fault plane, mainly distributed on the edge of the co-seismic fault, between the two faults. This study provides new data to better understand the seismic mechanism of this earthquake.